2013
DOI: 10.1161/circulationaha.113.001952
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Interpretation With Visual Assessment and Quantitative Coronary Angiography in Patients Undergoing Percutaneous Coronary Intervention in Contemporary Practice

Abstract: Background Studies conducted decades ago described substantial disagreement and errors in physicians’ angiographic interpretation of coronary stenosis severity. Despite the potential implications of such findings, no large-scale efforts to measure or improve clinical interpretation were subsequently made. Methods & Results We compared clinical interpretation of stenosis severity in coronary lesions with an independent assessment using quantitative coronary angiography (QCA) in 175 randomly selected patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(57 citation statements)
references
References 36 publications
2
54
0
1
Order By: Relevance
“…Our results were similar and confirm in a larger population previous studies describing the difference observed between VE and QCA. [34][35][36] …”
Section: Comparison Of Ve and Qca With Ds Severitymentioning
confidence: 99%
“…Our results were similar and confirm in a larger population previous studies describing the difference observed between VE and QCA. [34][35][36] …”
Section: Comparison Of Ve and Qca With Ds Severitymentioning
confidence: 99%
“…Third, QCA is mainly used for research purposes, and is rarely performed in daily clinical practice, where the degree of stenosis is intuitively judged by the visual estimation. Visual assessment overestimates stenosis more than QCA measurement in highly stenotic lesions, while it underestimates stenosis in mildly stenotic ones 20, 21. It could be possible that the suboptimal results might be underestimated by visual estimation.…”
Section: Discussionmentioning
confidence: 99%
“…Even when expert observers perform the visual assessment of the coronary arteries, inter-observer variabilities can be quite high [3]. Despite the fact that this is very well known, the most recent studies on this subject were made in the early 1990s, and to reveal the current status of this issue, Nallamothu et al [6] carried out a project called the "Assessing Angiography (A2) Project" as follows: In seven large hospitals in the United States, coronary angiographies of PCI-administered patients were selected randomly, the intervened stenosis was measured with quantitative methods (quantitative coronary angiography [QCA]) and compared to the visual assessment of the physician who carried out the process. In the study, the stenosis percentage of the physicians who read the lesions visually was found to be 84.2 ± 10.1 on average, and lesion severity was evaluated as ≥ 70% in 213 of the 216 evaluated patients.…”
Section: Discussionmentioning
confidence: 99%